Impacts and Lessons Learned of the First Three COVID-19 Waves on Cross-Border Collaboration in the Field of Emergency Medical Services and Interhospital Transports in the Euregio-Meuse-Rhine: A Qualitative Review of Expert Opinions - Sommer, Anja; Rehbock, Cassandra; Vos, Clara; Borgs, Christina; Chevalier, Sabrina; Doreleijers, Simone; Gontariuk, Marie; Hennau, Sofie; Pilot, Eva; Schröder, Hanna; Van der Auwermeulen, Loth; Ghuysen, Alexandre; et al. (Frontiers in Public Health, 2022)
Background: In the Euregio-Meuse-Rhine (EMR), cross-border cooperation is essential for resource-saving and needs-based patient care within emergency medical service (EMS) systems and interhospital transport (IHT). However, at the onset of the COVID-19 pandemic, differing national measures highlighted the fragmentation within the EU in its various approaches to combating the pandemic. To assess the consequences of the pandemic in the EMR border area, the aim of this study was to analyze the effects and "lessons learnt" regarding cross-border collaboration in EMS and IHT. Method: A qualitative study with 22 semi-structured interviews was carried out. Experts from across the EMR area, including the City of Aachen, the City region of Aachen, the district of Heinsberg (Germany), South Limburg (The Netherlands) and the province of Limburg as well as Liège (Belgium), took part. The interviews were coded and analyzed as follows: changes in cross-border collaboration prior to and during COVID-19, contrasts between national measures and cross-border agreements, as well as missed opportunities and lessons learnt during the pandemic. Results: Each country, also within the EMR area, addressed the pandemic individually with national measures. Cross-border cooperation was hardly or not at all addressed at national level during political decision- or policymaking. Previous direct communication at personal level was replaced by national procedures, which made regular cross-border cooperation significantly more difficult. The cross-border transfer regulations of COVID-19 patients proved to be complex and led, among other things, to patients being transported to a hospital far outside the border region. Cooperation continues to be seen as valuable and Euregional emergency services such as hospitals work well together, albeit to different degrees. The information and data exchange should, however, be more transparent to use resources more efficiently. Conclusion: Euregional cooperation is seen as essential but improvable. The following recommendations can be drawn from the findings. Regular meetings and learning from one another is essential. Regional cross-border agreements need to be better known and educated. Additionally understanding and recognizing their importance at national level is important. The determination of synergies and best practice are further approaches to support cross-border collaboration especially in future crisis situations.